Childhood, Schooling, and Universal Morality. Issue 13 (December 2013) - Kennedy, David
This chapter contrasts the aims of progressive and traditional state-mandated schooling, and argues that the former represents a new form in the history of Western education, oriented to individual, social and moral reconstruction rather than reproduction, and guided by the evolutionary possibilities inherent in human neoteny. The school is identified as a key site for the reconstruction of civic virtue in its role as a "just community" or embryonic society grounded in the principles and practices of participatory democracy.